Clinical outcomes of initially asymptomatic patients with COVID-19: a Korean nationwide cohort study. (1st January 2021) - Park, Hayne Cho; Kim, Do Hyoung; Cho, Ajin; Kim, Juhee; Yun, Kyu-sang; Kim, Jinseog; Lee, Young-Ki
Abstract: Background: This study was performed to compare severe clinical outcome between initially asymptomatic and symptomatic infections and to identify risk factors associated with high patient mortality among initially asymptomatic patients. Methods: In this retrospective, nationwide cohort study, we included 5621 patients who had been discharged from isolation or died from COVID-19 by 30 April 2020. The mortality rate and admission rate to intensive care unit (ICU) were compared between initially asymptomatic and symptomatic patients. We established a prediction model for patient mortality through risk factor analysis among initially asymptomatic patients. Results: The prevalence of initially asymptomatic patients upon admission was 25.8%. The mortality rates were not different between groups (3.3% vs. 4.5%, p = .17). However, initially symptomatic patients were more likely to receive ICU care compared to initially asymptomatic patients (4.1% vs. 1.0%, p < .0001). The age-adjusted Charlson comorbidity index score (CCIS) was the most potent predictor for patient mortality in initially asymptomatic patients. Conclusions: The mortality risk was not determined by the initial presence of symptom among hospitalized COVID-19 patients. The CCIS was the most potent predictors for mortality. The clinicians should predict the risk of death by evaluating age and comorbidities but not the initial presence of symptom. Key messages: The mortality rate was not different between initially asymptomatic and symptomatic patients. Symptomatic patients were more likely to admitted to the intensive care unit. Age and comorbidities were the potent risk factors for mortality.